(untitled) (Journal of Chemical Engineering, 2017)
In this work, activated carbon was prepared from low cost agricultural by-product rice husk and NaOH was used as chemical activating agent. The characterization of rice husk activated carbon (RHAC) was performed by Scanning Electron Microscope (SEM) and BET surface analyzer. In addition, the proximate analysis and Boehm titration was conducted to investigate RHAC properties and surface function groups. The adsorption of an organic pollutant (phenol) using RHAC was studied by the batch method. It was established that phenol adsorption by RHAC reached equilibrium at about 2640 min and is more compatible with Langmuir adsorption isotherm with respect to Freundlich isotherm. Phenol adsorption capacity of RHAC was found to be 17.123 mg g?1.The phenol adsorption kinetics corresponds well with pseudo first order model. Journal of Chemical Engineering, Vol. 29, No. 1, 2017: 29-33